P. Dickinson (ed.), 'Chamber Music (James Joyce). Thirty-two Songs for High Voice and Piano by G. Molyneux Palmer' (2020); 'James Joyce’s Favourite Songs: Chamber Music/The Joyce Book', M. Hill, P. Dickinson & M. Dickinson (Heritage Records, 2020) (Journal of the Society for Musicology in Ireland, 2023)
A review of Peter Dickinson (ed.), Chamber Music (James Joyce). Thirty-two Songs for High Voice and Piano by G. Molyneux Palmer (Tewkesbury: Goodmusic Publishing, 2020). ISMN M-2223-1494-8; James Joyce’s Favourite Songs: Chamber Music / The Joyce Book; Martyn Hill, tenor & Peter Dickinson, piano (Chamber Music); Meriel Dickinson, mezzo & Peter Dickinson, piano (Joyce Book) (CD, Heritage Records HTGCD 175, 2020).